Prinsip dan Jenis Tahapan Persidangan Hukum Acara Perdata - Misbachul Fitri, Abd. Basit; Hidayati, Erifah (USRATUNA: Jurnal Hukum Keluarga Islam, 2025)
This article examines the principles and stages of civil procedural proceedings in Indonesia as an effort to realize a judicial system that is simple, fast, and low-cost. The study is motivated by the high number of civil cases resolved through litigation, which has led to case backlogs and reduced judicial efficiency. Using a normative juridical approach, this research analyzes statutory regulations, legal doctrines, and civil court practices. The discussion focuses on the stages of civil proceedings at the court of first instance, beginning with the initial hearing that includes the reading of the statement of claim and the mandatory mediation process, followed by the stages of pleadings, evidence, conclusions, and judgment. The article also elaborates on the possible outcomes of the first hearing, such as default judgments (verstek), dismissal of claims, settlement judgments, and the continuation of proceedings when mediation fails. Furthermore, this study discusses the fundamental principles of civil procedure, including the principle of open court hearings, the principle of audi et alteram partem, judicial impartiality, as well as the principles of justice, equality, and legal certainty. The study concludes that the consistent application of procedural principles and stages, accompanied by the optimization of mediation, is essential to enhance the effectiveness of civil dispute resolution and to strengthen public trust in the judiciary.